India's Strategy in Reducing Palm Oil Import and Its Impacts to Bilateral Trade with Indonesia - Tofan Mahdi (Universitas Airlangga, 2023)
This article tries to analyze the strategy of Indian government in reducing its trade deficit through the import reduction of several main commodities including the palm oil. This research also seeks the impacts of the palm oil reduction in India towards India-Indonesia bilateral trade, as Indonesia is one of India's main trade partners and largest exporter of palm oil to India. This research used literature study within content analysis to find the bilateral trade between India and Indonesia, also the impacts of India palm oil import's reduction. The main data of research are secondary data from trusted and reputable news relating India palm oil imports from Indonesia. The result of study found that Indonesia needs to pursue efforts of trade diplomacy effectively so that the Indian strategy to cut imports will not be too impactful to the performance of its exports to India. This research enriches literature study about bilateral trade especially in India-Indonesia palm oil context. In practical implication, this research bring any recommendation to related stakeholder about bilateral trade strategy taken by Indonesian government.